2017
DOI: 10.1002/jnr.24101
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase inhibition triggers inflammatory responses in the brain of male rats exposed to ischemia‐reperfusion injury

Abstract: Nitric oxide (NO) derived from endothelial NO synthase (eNOS) plays a role in preserving and maintaining the brain's microcirculation, inhibiting platelet aggregation, leukocyte adhesion, and migration. Inhibition of eNOS activity results in exacerbation of neuronal injury after ischemia by triggering diverse cellular mechanisms, including inflammatory responses.To examine the relative contribution of eNOS in stroke-induced neuroinflammation, we analyzed the effects of systemic treatment with l-N-(1-iminoethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Therefore, the major contributor to the preconditioning effect in the transient hypoxia-ischemia model was the antioxidant effect and the preservation of NO bioavailability through NOS3 expression. As reported in a similar hypoxia-ischemia model, NOS3 is essential in the preservation and maintenance of microcirculation, inhibiting platelet aggregation, leukocyte adhesion, and migration and decreasing the inflammatory response [ 32 ]. The increased expression of NOS3 induced by zinc might be associated with the zinc finger protein ZFP580 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the major contributor to the preconditioning effect in the transient hypoxia-ischemia model was the antioxidant effect and the preservation of NO bioavailability through NOS3 expression. As reported in a similar hypoxia-ischemia model, NOS3 is essential in the preservation and maintenance of microcirculation, inhibiting platelet aggregation, leukocyte adhesion, and migration and decreasing the inflammatory response [ 32 ]. The increased expression of NOS3 induced by zinc might be associated with the zinc finger protein ZFP580 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have gained extensive attention, and could become a novel therapeutic target for the treatment of SCI. A large number of studies have shown that miR-155 is a broad regulator of inflammatory mediators, and plays a key regulatory role in immune and inflammatory disorders [34,35,36,37]. The development of neurodegenerative diseases is closely correlated with immunity and inflammation, suggesting that miR-155 may be a novel target for its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…accumulating evidence has indicated that activated microglia are the primary source of immunomodulatory molecules, such as cytokines, chemokines and free radicals, in the brain (16)(17)(18); these molecules are closely associated with secondary brain injury and brain tissue repair in ischemic stroke (16)(17)(18). in addition, some molecules, including soluble Fas ligand (19) and endothelial nitric oxide synthase (20,21), which are generated by other cells, such as neurons and endothelial cells, have also been identified to affect the stroke outcome through interacting with microglia in the brain following ischemic stroke (19). Therefore, investigating microglial changes and their function is crucial to understanding ischemic stroke pathophysiology.…”
Section: Modulators Of Microglia Activation and Polarization In Ischementioning
confidence: 99%
“…miRNA-155. Increased expression levels of miRNA-155 have been demonstrated to be associated with the neuroinflammatory responses (20,107). in lPS-activated microglia, miRNA-155 expression levels were significantly increased, which could target suppressor of cytokine signaling 1 to trigger M1 microglia-mediated inflammatory responses and aggravate brain damage (18).…”
Section: Nrfmentioning
confidence: 99%